The characteristics of Zn–5Al–2Mg coating on low carbon steel by two-step galvanizing method - Huan-Chang Liang; Jing-Tong Yang; Chaur-Jeng Wang (Journal of Materials Research and Technology, 2024)
The aim of this work is to characterize the complicated microstructure of a multilayer material that has been produced using a two-step batch galvanizing technique, with a particular focus on its extraordinary resistance to corrosion. The corrosion testing was performed using cyclic salt spraying, which involved the use of a salt mist chamber, wet chamber, and dry chamber. The results indicated that the Zn–5Al–2Mg (ZMA) coating system consists of four distinct layers: α, β, θ, and π layers. The top layer consisted of ternary and binary eutectic phases, whereas the central section had a branch-like Fe4Al13 phase. A continuous layer of Fe4Al13 was produced at an interface with the substrate. After undergoing 270 corrosion cycles, the coating demonstrated the capability to generate corrosion products that were dense and compact, including Zn5(OH)6Cl2H2O, Zn5(CO3)2(OH)6, and Mg6Al2(CO3)(OH)16⋅H2O. The corrosion products inhibited the corrosive substance from reaching the steel substrate, hence enhancing the durability of the coating.